Enzyme kinetics in confined geometries at the single enzyme level. Issue 7 (1st March 2022) - Murahara, Hisashi; Kaji, Noritada; Tokeshi, Manabu; Baba, Yoshinobu
Abstract : Different confinement, femtoliter chambers and molecular crowders revealed the effects on the catalytic rates of β-galactosidase at the single molecule level. Abstract : The effects of increased confinement on the catalytic rates of individual enzyme molecules were studied at the single molecule level using femtolitre chambers and molecular crowders. According to the increase of confinement, from micro to nanometer cubic space in the chambers, the hydrolysis rate of β-galactosidase (β-gal) decreased to one-tenth of the rate in bulk. When molecular crowders suppressed the diffusion rates that reduced the collision chance of an enzyme and a substrate, the hydrolysis rate also decreased, which happened also in the case of femtolitre chambers. However, their kinetic trend was different especially from the viewpoint of the diffusion rates in diffusion-limited space. These data suggested that cell or organelle-scale confined environments might affect the kinetics of biochemical reactions and emphasized the importance of understanding enzyme kinetics in the in vivo environment.